Character Education in the Poetry Collection of Kidung Cisadane by Rini Intama: A Study of Literary Reception - Endang Sulistijani; Sangaji Niken Hapsari; Mirza Ghulam Ahmad (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The method used in this study is descriptive qualitative. Data were collected by distributing questionnaires to 20 respondents. The objectives of this study were to determine the understanding and responses of readers, namely junior high school teachers in Pasar Rebo District about the collection of Kidung Cisadane poems by Rini Intama and to increase teachers' knowledge about literary assessment. From 704 data on the value of character education which is the result of the literary reception of the teachers to the collection of Kidung Cisadane poems, the results obtained are the religious aspect totaling 119 data or about 16.9%, the cultural aspect totaling 212 data or about 30.1%, the environmental aspect amounting to 203 data or approx. 28.8% and aspects of self-potential amounted to 170 data or about 24.1%. So, the dominant aspects of character education are cultural aspects, environmental aspects, self-potential aspects, and religious aspects.Keywords: Poetry, character education, literary reception.